Possibility to Use Solar Chimney to Improve Stack Ventilation in Tropical Climate - Nugroho, Agung Murti; Ahmad, Mohd Hamdan (Fakulti Alam Bina, UTM, 2006)
The climatic conditions of the tropical regions are characterized by high air temperatures, high relative humidity and very low wind speeds, which make the environmental conditions uncomfortable. A good dwelling design can keep the indoor environment favorable and comfortable during most of the year without the use of any mechanical devices. Depending on ambient conditions, natural ventilation may lead to indoor thermal comfort without mechanical cooling. However, in cases where the wind effect is not well captured or outdoor wind speed is very low, then stack ventilation may be a viable alternative. Stack ventilation standing involved temperature difference experiments which can be done using both experimental and numerical study. This paper evaluates the possibilities of use of solar chimney to improve stack ventilation in Malaysia’s climatic conditions. The use of solar chimneys as stack ventilation in buildings is one way to increase natural ventilation and, as a consequence, improve indoor air quality. The discussion of previous researches indicated that application of solar chimney strategy can increase ventilation performance in the room with optimize configuration variable. Based on the above results a next strategy will be developed to improve stack ventilation.